2007
DOI: 10.1523/jneurosci.5075-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilins and Their Ligands Are Important in the Migration of Gonadotropin-Releasing Hormone Neurons

Abstract: Gonadotropin-releasing hormone (GnRH) neurons in the hypothalamus play an important role in reproductive function. These cells originate in the nasal compartment and migrate into the basal forebrain in association with olfactory/vomeronasal nerves in embryonic life in rodents. Here, we studied the role of neuropilins and their ligands, semaphorins, in the development of the olfactory-GnRH system. We focused on Neuropilin-2 knock-out (Npn-2 ؊/؊ ) mice, because they are known to display defasciculation of olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 59 publications
3
76
0
6
Order By: Relevance
“…S1A-D). NRP2, the receptor for semaphorin 3F, is highly expressed by a subset of vomeronasal sensory neurons in rodent embryos and along vomeronasal axons innervating the AOB (Cariboni et al, 2007;Cloutier et al, 2002). Moreover, Nrp2 −/− mice display a GnRH migratory defect followed by reduced fertility and hypogonadism, supporting the direct involvement of neuropilins and their ligands in the establishment of the GnRH neuroendocrine system (Cariboni et al, 2007).…”
Section: Development Of the Vnn/tn And Gnrh Neuron Migrationmentioning
confidence: 90%
“…S1A-D). NRP2, the receptor for semaphorin 3F, is highly expressed by a subset of vomeronasal sensory neurons in rodent embryos and along vomeronasal axons innervating the AOB (Cariboni et al, 2007;Cloutier et al, 2002). Moreover, Nrp2 −/− mice display a GnRH migratory defect followed by reduced fertility and hypogonadism, supporting the direct involvement of neuropilins and their ligands in the establishment of the GnRH neuroendocrine system (Cariboni et al, 2007).…”
Section: Development Of the Vnn/tn And Gnrh Neuron Migrationmentioning
confidence: 90%
“…Consistently, although the expression of Nrp genes is greatly reduced in the mutants, it is the Pax6 + cells originated from the CGE that are severely affected (Figs 4,5;supplementary material Figs S6,S9). It has been reported that Nrp genes are required to mediate the migration of the GABAergic interneuron, cortical neuron, GnRH neuron and facial nerve neuron Chen et al, 2008;Cariboni et al, 2007;Schwarz et al, 2004). In addition to the cell migration, Nrp genes also play crucial roles in axon guidance.…”
Section: Pax6mentioning
confidence: 99%
“…42 Adult Nrp2-null mice have fewer GnRH neurons in the hypothalamus, and this is accompanied by infertility. 43 Because Sema3f-and Nrp2-null mice have defasciculated olfactory nerves, 44,45 the GnRH defect is at least in part due to abnormal cell migration on a defective axonal substrate. However, GnRH neurons themselves also express NRP2, and they are repelled by SEMA3F in vitro.…”
mentioning
confidence: 99%
“…However, GnRH neurons themselves also express NRP2, and they are repelled by SEMA3F in vitro. 43 This raises the possibility that SEMA3F/ NRP2 signaling may play a second, more direct role in GnRH neuron guidance. Finally, GnRH neurons express NRP1 and respond to VEGF164 and SEMA3A in vitro, 43 and loss of SEMA3A results in guidance errors of subsets of olfactory axons.…”
mentioning
confidence: 99%
See 1 more Smart Citation